Perception of São José dos Campos population about chronic kidney disease (Research, Society and Development, 2023)
Chronic kidney disease (CKD) is the progressive and irreversible loss of kidney function. It is a public health issue, and studies indicate that it affects more than 10% of the global population. Despite its severity, a low level of knowledge about this disease has been observed in various populations. Therefore, the objective of this study is to assess the level of understanding of CKD among the residents of São José dos Campos. This is a quantitative, descriptive, cross-sectional study in which a standardized questionnaire with objective questions was used for data collection. Following the established inclusion and exclusion criteria, 21 individuals were excluded, leaving 136 in the final sample. Concerning gender, 83 women and 51 men responded to the questionnaire, with 2 individuals selecting the "prefer not to disclose" option. There was greater participation from individuals aged between 21 and 29 and those aged between 40 and 49. The survey revealed that the level of education directly influences the level of knowledge about the disease; in other words, the lower the level of education, the less knowledge individuals have about the subject. It was observed in this study that the population has a low level of knowledge about this disease, its risk factors, preventive measures, and symptoms. This highlights the need to focus on public health interventions, aiming to raise public awareness, democratize access to information, and make the population less susceptible.